Innovations in Remote Sensing and Photogrammetry - Jones, Simon.; Reinke, Karin. (Lecture Notes in Geoinformation and Cartography,, 2009)
Remote sensing of our environment is becoming increasingly accessible and important in todays society. This book aims to highlight some of the broad and multi-disciplinary applications, and emerging practices, that remote sensing and photogrammetric technologies lend themselves to. The papers have been selected from the 13th and 14th Australasian Remote Sensing and Photogrammetry Conferences given by experts in remote sensing, spatial analysis and photogrammetry from across the Asia Pacific region. They are presented here as a collection of peer reviewed papers covering research into areas such as data fusion techniques and their applications in environmental monitoring, synoptic monitoring and data processing, terrestrial and marine applications of remote sensing, and photogrammetry.